Sport mega-events and public opposition: A sociological study of the London 2012 Olympics - Giulianotti, R.; Armstrong, G.; Hales, G.; Hobbs, D. (Journal of Sport and Social Issues, 2015)
This article examines the diverse forms of public opposition, protest, criticism, and complaint in the United Kingdom on the staging of the 2012 Olympic and Paralympic Games in London. Our discussion draws heavily on empirical research, primarily fieldwork and interviews in East London with local residents, opposition groups, business people, politicians, and other stakeholders. The article is separated into three main parts. First, we explore the setting and political-economic context for London 2012. The main Olympic setting—the London Borough of Newham—features very high levels of poverty and ethnic diversity. We argue that London 2012 represented a form of "festival capitalism" that was part of a broader set of "New Right two-step" policies in poor urban areas, involving initial Keynesian investment, followed by a deeper and far-reaching array of neo-liberal measures. Second, in the main part of the article, we identify and examine, in turn, six forms of public conflict, criticism, and complaint that centered on the Games, specifically national criticisms (e.g., on distribution of Olympic resources), local criticisms (e.g., on lack of jobs and business benefits), issue-specific campaigns (e.g., on the environment), "glocal" protests against specific nations and sponsors (e.g., campaigns against BP, Dow, and Rio Tinto), neo-tribal transgressions and situationist spectacles (e.g., mass cycle rides near Olympic venues), and anti-Olympic forums and demonstrations (e.g., critical web sites, multi-group marches). Third, we set out briefly the importance of conducting research into critics and opponents of sport mega-events, and discuss different arguments on how the social impact of protest movements might have been intensified at London 2012. The findings in this article may be extended to examine critical public responses to the hosting of other mega-events in different settings.